Role of frequency volume chart for the assessment of urinary incontinence in men - Samaddar, Debasis; Pal, Dilip Kumar (International Journal of Research in Medical Sciences, 2018)
Background: This study was conducted to evaluate the role of FVC (frequency volume chart) in the male patient with urinary incontinence. That will definitely help to evaluate patient’s objective lower urinary tract symptoms including incontinence and guide to manage those symptoms. But there are less number of reported studies showing role of FVC in men with urinary incontinence. Methods: Male patient (19-60 years) presenting with incontinence symptoms from 1st February 2018 to 30th July 2018, were enrolled in the study. They were asked to record the time and volume of each oral fluid intake, voided volume for 3 consecutive days and put tick in the column of incontinence in the FVC if present. Results: Total 205 male patients presented with incontinence symptoms were evaluated, they were divided into 3 age groups (19-32, 33-46 and 47-60 years). Mean incontinence were found 2.65 (19-32 years). 2.99 (33-46 years) and 3.13 (47-60 years). In 47-60 years group total oral fluid intake is positively correlated with frequency (p <0.05) but not in other groups. Correlation of Nocturia with incontinence (p >0.05) and frequency with incontinence (p >0.05) were not statistically significant in any age groups. Conclusions: The FVC is the registration of voiding parameters by patient in his own environment. Assessment of lower urinary tract symptoms based on a history alone is not accurate, value of FVC are found to be consistent and accurate, so it will guide us to initiate management in male with urinary incontinence and also help to assess treatment responsiveness.